Life Satisfaction during Forced Social Distancing and Home Confinement Derived from the COVID-19 Pandemic in Spain - Gonzalez-Bernal, Jerónimo J (Int J Environ Res Public Health, 2021)
Life satisfaction is one of the main dimensions of well-being related to psychological factors, being essential for a person to adjust to difficult circumstances. The restrictive measures adopted to minimize the diffusion of the coronavirus disease (COVID-19) could alter the subjective dimension of well-being, so the objective of this study was to determine the factors related to life satisfaction of the Spanish population during forced home confinement derived from the COVID-19 pandemic. A cross-sectional study was designed, based on an online survey, and disseminated through the main social networks, which included the Satisfaction with Life Scale (SWLS) and sociodemographic and COVID-19-related variables. The possible relationships between the different variables were studied using univariate and multivariable regression analyses. A total of 3261 subjects participated in the study. Factors associated with greater personal life satisfaction were fewer days of home confinement (β = (−0.088); p ≤ 0.001), the perception of having received enough information (β = 0.076; p ≤ 0.001), having private access to the outside (β = 0.066; p ≤ 0.001), being employed (β = 0.063; p ≤ 0.001), being male (β = 0.057; p = 0.001) and not having been isolated (β = 0.043; p = 0.013). The results of this study provide novel information about the profiles of people related to greater well-being and life satisfaction during forced social distancing and home confinement, but more studies are needed to help to understand and complement these findings.